Prevalence and Unmet Need for Mental Healthcare of Major Depressive Disorder in Community-Dwelling Chinese People Living With Vision Disability - Zhong, Bao-Liang; Xu, Yan-Min; Li, Yi (Frontiers in Public Health, 2022)
Objective: Mental health services have been recognized as an essential part of the comprehensive eye care services, but data regarding the mental health of people living with vision disability (PLwVD) remain very limited. This study examined the epidemiology of major depressive disorder (MDD) among Chinese PLwVD, as well as their perceived needs for and utilization of mental health services. Methods: By using stratified cluster sampling method, a total of 1753 PLwVD were successfully recruited from 73 urban communities and 169 rural villages in Wuhan, China, and interviewed with the Mini-international Neuropsychiatric Interview 5.0. Standardized questions were used to measure perceived mental healthcare needs and use of mental health services of PLwVD with MDD. Results: The one-month prevalence of MDD was 24.4%. Among the PLwVD with MDD, 26.0% perceived needs for mental healthcare and only 1.2% sought treatment from mental health specialists for their emotional problems. Factors associated with MDD were middle age (vs. young adulthood, odds ratio [OR]=1.96, P<0.001), older adulthood (vs. young adulthood, OR=1.79, P=0.004), being never-married (vs. married, remarried, and cohabiting, OR=1.96, P<0.001), being separated, divorced, and widowed (vs. married, remarried, and cohabiting, OR=12.30, P<0.001), a low level of objective social support (vs. high, OR=1.83, P<0.001), currently drinking (OR=1.81, P<0.001), having childhood-onset eye conditions (OR=1.89, P=0.005), and having difficulties in performing daily activities (OR=2.78, P<0.001). Conclusions: Chinese PLwVD are at high risk for MDD and have a high level of unmet need for mental healthcare. Public strategies are warranted to improve the mental health literacy of PLwVD and make the mental health services available, accessible, and affordable for PLwVD.